Mental health, permanent housing, and peer support through community living in the Fairweather Lodge: implementation through collaboration. Issue 1 (16th March 2015) - Bermingham, Charles; Manlick, Christopher F.; Liu, William Ming
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explain the history of the Fairweather Lodge Program, its utility, the development of one program in a small Midwestern city, the role of psychology, and the importance of disseminating information about the program to combat homelessness. Design/methodology/approach – This paper takes a short case study approach to describing the evolution of a peer support-based housing program for individuals with serious mental illness and a history of homelessness. Findings – The Fairweather Lodge facilitates peer support, community engagement, stable housing, and work engagement in those struggling with mental illness and homelessness. Originality/value – The Fairweather Lodge Program is a program intended to support the mental health and employment needs of individuals with severe mental illness who are at increased risk of homelessness. Housing alone often does not address the complex needs of chronically homeless individuals.